Understanding the Pathophysiology of Congenital Vestibular Disorders: Current Challenges and Future Directions - Peusner, Kenna D.; Bell, Nina M.; Hirsch, June C.; Beraneck, Mathieu; Popratiloff, Anastas (Frontiers in Neurology, 2021)
In congenital vestibular disorders (CVDs), children develop an abnormal inner ear before birth and face postnatal challenges to maintain posture, balance, walking, eye-hand coordination, eye tracking, or reading. Only limited information on inner ear pathology is acquired from clinical imaging of the temporal bone or studying histological slides of the temporal bone. A more comprehensive and precise assessment and determination of the underlying mechanisms necessitate analyses of the disorders at the cellular level, which can be achieved using animal models. Two main criteria for a suitable animal model are first, a pathology that mirrors the human disorder, and second, a reproducible experimental outcome leading to statistical power. With over 40 genes that affect inner ear development, the phenotypic abnormalities resulting from congenital vestibular disorders (CVDs) are highly variable. Nonetheless, there is a large subset of CVDs that form a common phenotype of a sac-like inner ear with the semicircular canals missing or dysplastic, and discrete abnormalities in the vestibular sensory organs. We have focused the review on this subset, but to advance research on CVDs we have added other CVDs not forming a sac-like inner ear. We have included examples of animal models used to study these CVDs. Presently, little is known about the central pathology resulting from CVDs at the cellular level in the central vestibular neural network, except for preliminary studies on a chick model that show significant loss of second-order, vestibular reflex projection neurons.